NILAI-NILAI PENDIDIKAN ISLAM DALAM RITUAL ADAT POSALAMA POGUNCI BULUA PADA ETNIS KAILI DI KELURAHAN PETOBO KOTA PALU - Hamlan Andi Baso Malla; Ardillah Abu; Husni Mubarak (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2021)
This study aims to determine the values ​​of Islamic education contained in the Posalama Pogunci Bulua Traditional Ritual of the Kaili Ethnic in Petobo Village, South Palu District. In this study, the author uses a type of qualitative descriptive research, which describes practically the object under study. Based on these data, the results of this study reveal that: (1) The process of implementing the traditional ritual of Posalama Pogunci Bulua on the Kaili ethnic group in the Petobo Village has several stages that must be carried out including the pokeso custom, preparing the materials used when the traditional ritual is carried out. and aqikah events. In carrying out these traditional rituals they still use the traditions inherited by their ancestors, namely by using symbols such as coconut, rice, candles, siranindi leaves, eggs, and money. These symbols have their own meanings. (2) For the Kaili ethnic community in Petobo Village, the traditional ritual of Posalama Pogunci Bulua is a form of gratitude to Allah SWT. for the children entrusted to them and also as a place of friendship between family and neighbors. While the meanings contained in the symbols used are not as material to be worshiped but as a prayer and hope for both parents to the child that they pray to Allah SWT. (3) In the review of Islamic education, the traditional ritual of posalama pogunci Bulua contains educational values ​​including the value of faith education, the value of moral education, and the value of social education.